PENGARUH EARNING POWER TERHADAP EARNING MANAGEMENT - Sarjito Surya; Dedi Rossidi Soetama; Ruly Ruliana (Akuntabilitas, 2016)
The aim of this research is to examine how big the effect of Earning Power based on Return on Assets (ROA dimension) toward Earning Management based on Discretionary Accruals (DAC dimension,).This research are using primary data, monthly financial reports on January to July 2014. The analytical method used is simple regression analysis which consists of classical assumption (autocorrelation test) and test of hypotheses (coefficient of determination and t test).The results from this research there is significantly positve effecting between Earning Power toward Earning Management from autocorrelation test with57.91%.DOI: 10.15408/akt.v9i1.3587